User's Satisfaction Levels Toward Sadeng Coastal Fishing Port Service at Gunungkidul Regency - I Gede Suweda Anggana Putera; Suadi Suadi; Siti Ari Budhiyanti (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2022)
Ensuring high-quality service is one of the most challenging aspects of managing fishing ports, including Sadeng Fishing Port. Service quality is important because it is one of the success determinants of port management. The port's prosperity is intimately tied to the quality of service given, which supports the port's role and function as a center for fishing activities. The study aimed to measure user satisfaction with service quality and which service indicators needed modification and maintenance to improve service quality in the Coastal Fishing Port (PPP). A survey of 45 port users, including fishermen, ship owners, traders, and fish processors, as well as the Fish Auction Site Manager and the Port Manager, was conducted in PPP Sadeng from August to October 2021. The information was analyzed using the Customer Satisfaction Index (CSI) and the Importance Performance Analysis (IPA). The study showed that the availability of basic, functional, and supporting facilities was 86.84 percent. Port users were satisfied to a degree of 65.20 percent, which is considered relatively satisfactory. To improve service quality, about six service attributes should be prioritized. The port personnel's ability to respond quickly to problems; the port personnel's responsiveness to users' complaints; the personnel's ability to provide security guarantees in using services; the cleanliness, orderliness, and comfort of the port physical condition; and the port facilities' arrangement, completeness, readiness, and cleanliness were among them. It was necessary to improve the provision of amenities, especially for the functional facilities; in the meantime, improving service quality should prioritize personnel reaction to problems and handling user complaints. Keywords: Customer Satisfaction Index, Importance Performance Analysis, Sadeng Coastal Fishing Port, Gunungkidul Regency